Improving Seventh Grade Students’ Reading Comprehension of Fantasy Stories through the Implementation of Jigsaw Cooperative Learning Model at MTs. Swasta Al-Hakimiyah Paringgonan - Kastiarni Nasition; Irmadani Parapat (PANTAK: Jurnal Penelitian Tindakan Kelas, 2026)
This study aimed to improve seventh-grade students’ reading comprehension of fantasy stories through the implementation of the Jigsaw Cooperative Learning model at MTs. Swasta Al-Hakimiyah Paringgonan. The research employed Classroom Action Research (CAR) based on the model of Kemmis and McTaggart, consisting of four stages: planning, action, observation, and reflection. The participants of this study were 33 seventh-grade students at MTs. Swasta Al-Hakimiyah Paringgonan. The data were collected through reading comprehension tests, classroom observations, interviews, field notes, and documentation. Quantitative data were analyzed using descriptive statistics by calculating students’ mean scores and the percentage of students achieving the Minimum Mastery Criterion (KKM), while qualitative data were analyzed through data reduction, data display, and conclusion drawing.The findings revealed that the implementation of the Jigsaw Cooperative Learning model significantly improved students’ reading comprehension of fantasy stories. The students’ mean score increased from 61.21 in the pre-test to 72.88 in Cycle I and 83.64 in Cycle II. The percentage of students achieving the Minimum Mastery Criterion also increased from 27.27% in the pre-test to 63.64% in Cycle I and 87.88% in Cycle II. In addition, classroom observations showed that students became more active, confident, collaborative, and motivated during the learning process. The Jigsaw activities helped students understand the elements of fantasy stories, including characters, settings, plot, conflicts, resolutions, and moral values through peer interaction and group discussions.Based on the findings, it can be concluded that the implementation of the Jigsaw Cooperative Learning model effectively improved seventh-grade students’ reading comprehension of fantasy stories. Therefore, this model is recommended as an alternative teaching strategy to create an interactive, collaborative, and student-centered reading environment in junior high school classrooms.